Notes on tiger beetles from Guinea-Bissau, with description of a new species of Cylindera Westwood (Insecta: Coleoptera, Cicindelidae) - Serrano, Artur R.m. (Zootaxa, 2007)
The biodiversity of tiger beetles collected in Guinea-Bissau during an Entomological Mission to this African country is given. Twenty species were identified, and their distribution in Guinea-Bissau is mapped. A new species is described: Cylindera (Ifasina) gulbenkiana Serrano, n. sp. (GUINEA-BISSAU, TOMBALI, Guilege). This is the first new tiger beetle species described from this country in the last 158 years. A key to the known species of Cylindera (Ifasina) of WestAfrica is given. Adults of tiger beetles were found by direct observation and by light trapping. An up-date of the tiger beetle species recorded for Guinea-Bissau gives a total of 35 species.